Research on Three-level Enrichment Method Based on 222Rn. Issue 1 (29th January 2023) - Wang, Yutao; Shan, Jian; Yang, Xiyu; Zhang, Hao; Li, Haoxuan
Abstract: Various low-concentration inert gases, including 222 Rn, 133 Xe, and 85 Kr, pollute the atmosphere near nuclear facilities (e.g., nuclear power plants or reprocessing plants). Owing to the detection limits of instruments, it has become urgent to determine the concentration of these gases efficiently and perform their online monitoring. However, current technologies are limited by low enrichment efficiencies. In this study, a high-pressure, low-flow, large-volume, and high-efficiency adsorption method has been proposed along with a high-temperature, low-pressure, high-flow, and small-volume rapid desorption and collection method, which are based on the gas enrichment principle of activated carbon. The results demonstrated that when dynamic adsorption was implemented using a two-level enrichment method, the final desorbed gas concentration was proportional to the volume ratio of both the large and small activated carbon beds. At a volume ratio of 15:1, 222 Rn concentration increased from 110 to 21, 016 Bq m −3 after the two-level enrichment; meanwhile, 222 Rn concentration increased from 110 to 42, 012 Bq m −3 after three-level enrichment. The three-level enrichment technology provides technical support for the enrichment of low-concentration inert gases in the environment, while offering an important technical foundation for improving the monitoring of low-concentration inert gases in specific environments as well as the atmospheric environment.